2011
DOI: 10.1186/1471-2458-11-190
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking among detained undocumented migrants: a cross-sectional study

Abstract: BackgroundAs in many European countries, access to care is decreased for undocumented migrants in the Netherlands due to legislation. Studies on the health of undocumented migrants in Europe are scarce and focus on care-seeking migrants. Not much is known on those who do not seek care.MethodsThis cross-sectional study includes both respondents who did and did not seek care, namely undocumented migrants who have been incarcerated in a detention centre while awaiting expulsion to their country of origin. A conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
(26 reference statements)
1
22
1
1
Order By: Relevance
“…For instance, in a cross-sectional study performed in the center for migrants of Lampedusa (Italy), attending migrants crossing the so-called "central Mediterranean route" [33] the most frequent diagnosis was scabies, skin infections, pediculosis and dermatitis, and also respiratory infections and varicella were the most represented infectious diseases, just quite different from the problems identified in this study, perhaps due to the specific characteristics of this route, very different from the route of the Strait of Gibraltar. Moreover, as mentioned, health problems related to exposure to high temperatures are especially frequent in illegal migratory movements such as across the Mexico-Arizona border [26,27] or, for example, it has been reported in immigrants who illegally access other countries in northern Europe such as the Netherlands, seeking care most frequently for injuries and dental problems [34]. Other studies also highlighted the mental health problems that have been identified among humanitarian migrants who access countries such as Australia where premigration potentially traumatic events and postmigration stressors were positively associated with posttraumatic stress disorder and severe mental illness [35], aspects that we have not detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a cross-sectional study performed in the center for migrants of Lampedusa (Italy), attending migrants crossing the so-called "central Mediterranean route" [33] the most frequent diagnosis was scabies, skin infections, pediculosis and dermatitis, and also respiratory infections and varicella were the most represented infectious diseases, just quite different from the problems identified in this study, perhaps due to the specific characteristics of this route, very different from the route of the Strait of Gibraltar. Moreover, as mentioned, health problems related to exposure to high temperatures are especially frequent in illegal migratory movements such as across the Mexico-Arizona border [26,27] or, for example, it has been reported in immigrants who illegally access other countries in northern Europe such as the Netherlands, seeking care most frequently for injuries and dental problems [34]. Other studies also highlighted the mental health problems that have been identified among humanitarian migrants who access countries such as Australia where premigration potentially traumatic events and postmigration stressors were positively associated with posttraumatic stress disorder and severe mental illness [35], aspects that we have not detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The same quoted Canadian experience further concludes that these crucial psycho-social and religious elements are "often overlooked in Canadian maternity settings [10]. " If looked for, the odds are in favour of the same conclusion in general, in Malta, as indeed elsewhere, such as Holland where :"These groups face similar problems, that is, the initial lack of knowledge on the Dutch health care system, language problems and difficulties arising in the communication with health care providers who have a different cultural background than the patient [11]. Such an ethnic barrier, at times in spite of correct interpretation (not to be universally assumed), has multiple facets from the moment of the patient entering the doctor's office to the point of departure.…”
Section: Communication Issuesmentioning
confidence: 99%
“…Between 2008 and 2012 Malta received, on average, the highest number of asylum seekers compared to its national population: 21.7 applicants per 1,000 inhabitants [4][5][6][7][8][9][10][11]. In 2011, most of these asylum applications were submitted by nationals of Somalia, Nigeria, Eritrea and Syria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of specialized mental health services, there are numerous barriers to the delivery and uptake of psychological interventions for refugees (WHO, 2015). These include communication difficulties such as language barriers and interpreter costs (Satinsky, Fuhr, Woodward, Sondorp, & Roberts, 2019), stigma around mental illness (Hassan, Ventevogel, Jefee-Bahloul, Barkil-Oteo, & Kirmayer, 2016), waitlists (Satinsky et al, 2019), and difficulties navigating within a foreign health care system (Dorn et al, 2011). Treatment programmes usually focus on single psychiatric disorders (such as PTSD), whereas many refugees suffer from multiple psychological problems (Thabet, Abed, & Vostanis, 2004).…”
Section: Introductionmentioning
confidence: 99%